Determining Farmers’ Awareness About Climate Change Mitigation and Wastewater Irrigation: A Pathway Toward Green and Sustainable Development - Sohail, Muhammad Tayyab; Elkaeed, Eslam B.; Irfan, Muhammad; Acevedo-Duque, Ángel; Mustafa, Sohaib (Frontiers in Environmental Science, 2022)
The present study was conducted in one of the major agriculture areas to check farmer’s awareness toward Climate change, adaptation measurements and use of wastewater for irrigation. A semi-structured questionnaire was adopted from existing literature, it was divided into different parts like demographic information, Use of wastewater for irrigation, farmer's livelihood assets, climate change deciding factor and adaptation measures, some statistical tools (Correlation and regression) were used to analyze the data. The farmers with enough resources and assets regarded themselves as safer and can have enough capacity to bear the negative impacts of climate change. Farmers’ Assets (FA) with Determinants of Climate Change (DCC) and Adaption Measures (AM) are highly significant with the correlation values .440 and .466 respectively and DCC with AM (.269). Gender with cultivated land .202, Waste Water Use (WWU) .419, Farmers’ Assets (FA) .766, Determinants of Climate Change (DCC) .381 and Adaption Measures (AM) .449 respectively. Floods and Droughts variables have shown a significant relationship with adaption measures (p-value 0.000 and coefficient 0.176) and (p-value 0.021 and coefficient 0.063). The study will aid in the implementation of effective monitoring and public policies to promote integrated and sustainable water development.